Diversified Communication and Harmony of Chinese culture: a historical investigation into the religious-culture exchanges among the Hans, Tibetans, and Mongolians - Wuhu Sun; Dorje Banbur; Yue Li (International Journal of Anthropology and Ethnology)
Abstract How can harmonious communication, integration, and coexistence among different ethnicities with distinct cultures be achieved in a multi-ethnic country? What lessons can we draw from China’s multi-ethnic cultural exchanges throughout history? Are Confucianism, Daoism, and Buddhism exclusive to the culture of the Central Plains? These questions are essential for forging a sense of the Chinese nation as one community and building a shared cultural home of the Chinese nation. Throughout Chinese history, the Han, Tibetan, and Mongolian ethnicities have engaged in mutual exchanges and integrations of their respective religious-cultures, fostering mutual promotion and collective growth, leaving behind valuable experiences that shaped the Chinese cultural pattern of “Diversified Communication and Harmony.” Drawing upon extensive literature and materials documenting the religious-culture exchanges and interactions among the Han, Tibetan, and Mongolian ethnicities since the Tang and Song dynasties, this article investigates the interaction, exchange, and integration history of religious-culture among these ethnicities, aiming to explore the historical evolution of this pattern of “Diversified Communication and Harmony”.